Charge‐Promoted Self‐Metalation of Porphyrins on an Oxide Surface. Issue 10 (14th January 2021) - Egger, Larissa; Hollerer, Michael; Kern, Christian S.; Herrmann, Hannes; Hurdax, Philipp; Haags, Anja; Yang, Xiaosheng; Gottwald, Alexander; Richter, Mathias; Soubatch, Serguei; Tautz, F. Stefan; Koller, Georg; et al.
Abstract: Metalation and self‐metalation reactions of porphyrins on oxide surfaces have recently gained interest. The mechanism of porphyrin self‐metalation on oxides is, however, far from being understood. Herein, we show by a combination of results obtained with scanning tunneling microscopy, photoemission spectroscopy, and DFT computations, that the self‐metalation of 2H‐tetraphenylporphyrin on the surface of ultrathin MgO(001) films is promoted by charge transfer. By tuning the work function of the MgO(001)/Ag(001) substrate, we are able to control the charge and the metalation state of the porphyrin molecules on the surface. Abstract : The self‐metalation of 2 H ‐tetraphenylporphyrin on the surface of MgO is believed to be feasible only at defect sites. It is shown that this reaction is promoted by charge transfer and does not necessarily require the presence of defects. Using ultrathin MgO films as substrate and tuning its work function allows the charge and metalation state of the adsorbed molecules to be controlled.